Adrenomedullin and Angiopoietin‐1 Additively Restore Erectile Function in Diabetic Rats: Comparison with the Combination Therapy of Vascular Endothelial Growth Factor and Angiopoietin‐1. (7th May 2013) - Nishimatsu, Hiroaki; Suzuki, Etsu; Nomiya, Akira; Niimi, Aya; Suzuki, Motofumi; Fujimura, Tetsuya; Fukuhara, Hiroshi; Homma, Yukio
Abstract Introduction Erectile dysfunction (ED) is a major health problem. We have shown that adrenomedullin (AM) restores erectile function in diabetic rats. Aim The aim of this study is to explore a better treatment for ED, we examined whether combination of AM and angiopoietin‐1 (Ang‐1) was more effective to treat ED than treatment with AM alone or Ang‐1 alone. We also compared the effect of the combination therapy with that of treatment with vascular endothelial growth factor‐A (VEGF‐A). Methods Male Wistar rats were injected with streptozotocin (STZ) to induce diabetes. Adenoviruses expessing AM (AdAM), Ang‐1 (AdAng‐1), and VEGF‐A (AdVEGF‐A) were injected into the penis 6 weeks after STZ administration. Erectile function, penile histology, and protein expression were analyzed 4 weeks after the injection of the adenoviruses. Main Outcome Measures Intracavernous pressure and mean arterial pressure were measured to evaluate erectile function. The morphology of the penis was analyzed by Elastica van Gieson stain and immunohistochemistry. The expression of α‐smooth muscle actin (SMA), VE‐cadherin and type I collagen was assessed by Western blot analysis. Results Infection with AdAM plus AdAng‐1 more effectively restored erectile function than infection with AdAM alone or AdAng‐1 alone. This combination therapy restored erectile function to a level similar to that observed in the age‐matched Wistar rats. Expression of SMA and VE‐cadherin increased more significantly in the AdAM plus AdAng‐1‐treated group than in the AdAM‐ or AdAng‐1‐treated group. Although AdVEGF‐A infection restored erectile function significantly, it also caused enlargement of the trabeculae of the cavernous body, aberrant angiogenesis, and overproduction of type I collagen. Conclusions These results suggested that combination therapy with AM and Ang‐1 potently restored erectile function and normal morphology of the cavernous body compared with VEGF‐A administration. This combination therapy will be useful to treat ED patients with a severely damaged cavernous body. Nishimatsu H, Suzuki E, Nomiya A, Niimi A, Suzuki M, Fujimura T, Fukuhara H, and Homma Y. Adrenomedullin and angiopoietin‐1 additively restore erectile function in diabetic rats: Comparison with the combination therapy of vascular endothelial growth factor and angiopoietin‐1. J Sex Med **;**:**–**.